ANALISIS PENGEMBANGAN USAHATANI UBI BANGGAI DI KECAMATAN BULAGI KABUPATEN BANGGAI KEPULAUAN - Enteding, Trianto; Karim, Sarah Febriana; Puspapratiwi, Dian; Yatim, Herwin (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2024)
Banggai Yams farming is an effort made by Banggai Yams farmers to get satisfactory results or profits to meet their daily needs. The purpose of this study is to find out the ways or strategies used in the development of Banggai Yams farming in Bulagi District, Banggai Islands Regency. This research will be carried out in Bulagi sub-district from June to August 2023. The population of 15 villages is more than 100 people, then the sample taken is 25% of the entire population with consideration of the location of respondents who are geographically scattered and the sampling technique used is a simple random sampling technique. The results showed that the right strategy in efforts to develop Ubi Banggai farming in the position of strategy or quadrant I is to support an aggressive strategy, namely the S-O (Strengths-Opportunities) strategy with a score obtained of 3.32. And the strategy applied to the development of Banggai yam farming in Bulagi District, Banggai Islands Regency by utilizing existing strengths and opportunities, namely by utilizing Banggai Yams as a substitute for rice, experienced in cultivating Banggai Yam, availability of labor, ease of marketing so that the threats faced such as relatively low prices, climate / weather, land ownership, lack of supporting institutions can be better minimized in order to increase in farmers' income.